Fraser Syndrome: Epidemiological Study in a European Population. Issue 5 (26th March 2013) - Barisic, Ingeborg; Odak, Ljubica; Loane, Maria; Garne, Ester; Wellesley, Diana; Calzolari, Elisa; Dolk, Helen; Addor, Marie‐Claude; Arriola, Larraitz; Bergman, Jorieke; Bianca, Sebastiano; Boyd, Patricia A.; et al.
Abstract Fraser syndrome is a rare autosomal recessive disorder characterized by cryptophthalmos, cutaneous syndactyly, laryngeal, and urogenital malformations. We present a population‐based epidemiological study using data provided by the European Surveillance of Congenital Anomalies (EUROCAT) network of birth defect registries. Between January 1990 and December 2008, we identified 26 cases of Fraser syndrome in the monitored population of 12, 886, 464 births (minimal estimated prevalence of 0.20 per 100, 000 or 1:495, 633 births). Most cases (18/26; 69%) were registered in the western part of Europe, where the mean prevalence is 1 in 230, 695 births, compared to the prevalence 1 in 1, 091, 175 for the rest of Europe (P = 0.0003). Consanguinity was present in 7/26 (27%) families. Ten (38%) cases were liveborn, 14 (54%) pregnancies were terminated following prenatal detection of a serious anomaly, and 2 (8%) were stillborn. Eye anomalies were found in 20/24 (83%), syndactyly in 14/24 (58%), and laryngeal anomalies in 5/24 (21%) patients. Ambiguous genitalia were observed in 3/24 (13%) cases. Bilateral renal agenesis was present in 12/24 (50%) and unilateral in 4/24 (17%) cases. The frequency of anorectal anomalies was particularly high (42%). Most cases of Fraser syndrome (85%) are suspected prenatally, often due to the presence of the association of renal agenesis and cryptophthalmos. In the European population, a high proportion (82%) of pregnancies is terminated, thus reducing the live birth prevalence to a third of the total prevalence rate. © 2013 Wiley Periodicals, Inc.